Pengaruh latihan fonasi vokal “a” berdasarkan lee silverman voice treatment loud terhadap kejelasan bicara pasien stroke iskemik - Rahayu, Sisri; Sujianto, Untung; Husna, Elfira; Ashra, Fauzi; Putra, Yuhendri; Liza, Fera (Holistik Jurnal Kesehatan, 2025)
Background: Speech nerve disorders due to stroke cause slurred speech. Lee Silverman Loud Voice Therapy can be applied using the Swanson technique to help stimulate the speech muscles. Purpose: To determine the effect of "a" vowel phonation training based on Lee Silverman Loud Voice Therapy on speech intelligibility in ischemic stroke patients. Method: This quasi-experimental study used a pretest-posttest non-equivalent control group approach, conducted from September to November 2024 at Dr. Achmad Mochtar Regional General Hospital, Bukittinggi. A purposive sampling method was used to select 22 participants, who were divided into intervention and control groups. Data were analyzed using a paired t-test with α ≤ 0.05. Results: In the intervention group, the average pretest score was 15 and the posttest score was 4.82. In the control group, the average pretest score was 16.91 and the posttest score was 16.45. A decrease in the average score indicates an improvement. The analysis showed an effect of "a" vowel phonation training with p = 0.001 (p ≤ 0.05). Conclusion: There is an effect of "a" vowel phonation training based on the Lee Silverman Voice Treatment Loud on speech intelligibility in ischemic stroke patients. A decrease in the mean speech intelligibility score indicates an increase in speech intelligibility. A lower score indicates better speech intelligibility. Suggestion: Future researchers should conduct further research with a larger sample size and implement the full training procedure, as well as considering other variables, such as severity, initial treatment time, stroke phase, other rehabilitation provided by healthcare facilities, comorbidities, family and friend support, and motivation.   Keywords: Ischemic Stroke; Lee Silverman Voice Treatment Loud; Speech Clarity; Vocal Phonation.   Pendahuluan: Gangguan saraf bicara akibat stroke menyebabkan ketidakjelasan bicara. lee silverman voice treatment loud dapat diterapkan dengan caring Swanson untuk membantu menstimulasi otot bicara. Tujuan: Untuk mengetahui pengaruh latihan fonasi vokal “a” berdasarkan lee silverman voice treatment loud terhadap kejelasan bicara pasien stroke iskemik. Metode: Penelitian quasi-eksperimen menggunakan pendekatan pretest posttest nonequivalent control group, dilakukan pada September-November 2024 di RSUD Dr. Achmad Mochtar Bukittinggi. Sampel diambil menggunakan purposive sampling dengan jumlah 22 partisipan yang terbagi dalam kelompok intervensi dan kontrol. Data dianalisis dengan T-Test (Paired-Test) α≤ 0.05. Hasil: Pada kelompok intervensi rata-rata ketika pre-test 15 dan post-test yaitu 4.82. Pada kelompok kontrol ketika pre-test yaitu 16.91 dan post-test yaitu 16.45. Nilai rata-rata yang menurun, menunjukkan perubahan yang membaik. Analisis menunjukkan terdapat pengaruh latihan fonasi vokal “a” dengan p = 0.001 (p ≤ 0.05). Simpulan: Terdapat pengaruh latihan fonasi vokal “a” berdasarkan Lee Silverman Voice Treatment Loud terhadap kejelasan bicara pasien stroke iskemik. Penurunan rata-rata menunjukkan nilai kejelasan yang membaik. Semakin turun nilai, maka semakin baik kejelasan bicara yang dialami. Saran: Bagi peneliti selanjutnya, dapat melakukan penelitian lebih lanjut dengan sampel yang lebih besar dan melakukan seluruh prosedur latihan serta memperhatikan variabel lain, seperti tingkat keparahan, waktu penanganan awal, fase stroke, rehabilitasi lain yang didapat dari faskes, penyakit komorbid, dukungan keluarga dan teman serta motivasi.   Kata Kunci: Fonasi Vokal; Kejelasan Bicara; Lee Silverman Voice Treatment Loud; Stroke Iskemik.